AI in education: boon or bane? / Sheela Paramasivam and PM Dr Alice Shanthi Kasawi @ Krisnan - Paramasivam, Sheela; Kasawi @ Krisnan, Alice Shanthi (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Much has been debated about artificial intelligence (AI) and whether this new technology of the century is a boon or bane. While many welcome AI and see it as a boon, others view it as a bane for the simple reason that they fear AI may replace human beings someday. So, what is AI? Artificial Intelligence (AI) refers to the development of computer systems that can perform tasks that typically require human intelligence (Limna et al., 2022). AI is becoming increasingly popular and used in many sectors, such as the business, finance, tourism, medicine, food and beverage, entertainment, and education sectors. In the education field, the current use of AI can be seen in Classroom/Behaviour Management, Lesson Planning, Language Learning, Test Preparation, Assessment, Learning Management Systems, Gamification, Staff Scheduling, Finance and many more. AI has gained prominence in education because it supports various learning platforms. For students, an example of a typically popular AI is ChatGPT. ChatGPT can assist students with homework questions, providing explanations and solutions to various academic topics. Therefore, artificial intelligence (AI) can improve education by enhancing teaching and learning outcomes. However, like any new technology, there are risks to its use.